Adaptation of an Obstetric Anesthesia Service for the Severe Acute Respiratory Syndrome Coronavirus-2 Pandemic: Description of Checklists, Workflows, and Development Tools. Issue 3 (25th September 2021) - Li, Y.; Ciampa, E.J.; Zucco, L.; Levy, N.; Colella, M.; Golen, T.; Shainker, S.A.; Lunderberg, J.M.; Ramachandran, S.K.; Hess, P.E.
Abstract : ( Anesth Analg . 2021;132:31–37) Health care workers have a significant risk of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) exposure and infection. Current guidelines detailing the management of patients with confirmed or suspected SARS-CoV-2 infection do not adequately address preparations aimed at mitigating SARS-CoV-2 infection risks associated with procedures specific to obstetric anesthesia. There is a need for workflows and checklists that maintain safety, provide effective care for patients with or without SARS-CoV-2 infection, and reduce waste during labor analgesia, cesarean neuraxial anesthesia, general anesthesia, and situations such as conversion of labor analgesia to cesarean anesthesia. This report discusses the COVID response workflows developed by the Beth Israel Deaconess Medical Center in Boston.